Beta-alanine supplementation enhances judo-related performance in highly-trained athletes - Andrade Kratz, C.; Salles Painelli, V.; Andrade Nemezio, K. M.; Pires da Silva, R.; Franchini, E.; Moura Zagatto, A.; Gualano, B.; Giannini Artioli, G. (Journal of Science and Medicine in Sport, 2017)
Objectives: In official judo competitions, athletes usually engage in 5-7 matches in the same day, performing numerous high-intensity efforts interspersed by short recovery intervals. Thus, glycolytic demand in judo is high and acidosis may limit performance. Carnosine is a relevant intracellular acid buffer whose content is increased with beta-alanine supplementation. Thus, we hypothesized that beta-alanine supplementation could attenuate acidosis and improve judo performance. Design: Twenty-three highly-trained judo athletes were randomly assigned to receive either beta-alanine (6.4 g day-1) or placebo (dextrose, same dosage) for 4 weeks. Methods: Performance was assessed before (PRE) and after (POST) supplementation through a 5-min simulated fight (randori) followed by 3 bouts of the Special Judo Fitness Test (SJFT). Blood samples were collected for blood pH, bicarbonate (HCO3-) and lactate determination. Results: Beta-alanine supplementation improved the number of throws per set and the total number of throws (both p < 0.05). Placebo did not change these variables (both p > 0.05). Blood pH and HCO3- reduced after exercise (all p < 0.001), with no between-group differences (all p > 0.05). However, the lactate response to exercise increased in the beta-alanine group as compared to placebo (p < 0.05). Conclusions: In conclusion, 4 weeks of beta-alanine supplementation effectively enhance judo-related performance in highly-trained athletes.